EXAMINING EARNINGS MANAGEMENT AND FIRM AGE: A QUANTITATIVE COMPARATIVE STUDY - Ruth Samantha Hamzah; Efva Octavina Donata Gozali; Nur Khamisah (JRAK, 2022)
This paper examines the association of firm age on earnings management (EM). We compared the large samples of 688 and 844 year-observation on listed firms in Indonesia stock exchange (IDX) and Singapore stock exchange (SGX), respectively. SGX is used as a benchmark of South East Asia (SEA) stock market. Despite SGX transaction has the highest rank in SEA stock exchange, yet the firm age average is newer than the IDX counterparts. Panel data regression was employed in analyzing the data. In addition, we conducted an anova pairwise t-test to examine the difference of firm age and EM depedency association in IDX and SGX. The result shows that both on IDX and SGX, firm age have a negative and significant effect towards EM. Moreover, it is found that there is a significant difference between the effect of firm age to EM in the firm listed on IDX and SGX.